Application of topical gentamicin ointment in the treatment of Nagashima‐type palmoplantar keratosis in children with a nonsense mutation - Shan Wang; Zhou Yang; Ying Liu; Huan Zhang; Zongyang Liu; Xiaoling Wang; Ying Li; Haihong Liu; Yonghong Yang; Lin Ma (Wiley, 2023)
ABSTRACT Importance Nagashima‐type palmoplantar keratosis (NPPK) is a hereditary dermatosis mostly caused by a nonsense mutation in SERPINB7. Despite the increasing interest in readthrough gentamicin treatment of NPPK, clinical evidence for this treatment is limited. Objective This study aimed to provide further evidence for the use of topical gentamicin in the treatment of NPPK in children with nonsense mutations. Methods We designed a bilaterally controlled study of topical gentamicin ointment. Children diagnosed with NPPK carrying nonsense mutations were enrolled in this study. A 0.1% gentamicin ointment was applied to one hand and an emollient to the other for 3 months. A bilateral comparison of the visual analog scale scores for clinical manifestations and safety was performed. Results Ten children with NPPK were included in this study. In comparison with the emollient side, the topical gentamicin side showed significant improvements in hyperkeratosis, erythema, maceration, and desquamation after 1 and 3 months of treatment (P < 0.05). However, hyperhidrosis and odor did not improve significantly. No adverse events were observed during the systemic safety monitoring examinations. Interpretation Topical gentamicin ointment showed good safety in the treatment of NPPK with nonsense mutations, indicating that it is a promising therapeutic choice in children with NPPK.